A racemic and enantiopure unsymmetric diiron(III) complex with a chiral o-carborane-based pyridylalcohol ligand: Combined chiroptical, magnetic, and nonlinear optical properties - Di Salvo, Florencia (2014)
The design of molecule-based systems combining magnetic, chiroptical and second-order optical nonlinear properties is still very rare. We report an unusually unsymmetric diiron(III) complex 1, in which three bulky chiral carboranylpyridinealkoxide ligands (oCBhmp-) bridge both metal ions and the complex shows the above-mentioned properties. The introduction of o-carborane into the 2-(hydroxymethyl)pyridine (hmpH) architecture significantly alters the coordination of the simple or aryl-substituted 2-hmpH. The unusual architecture observed in 1 seems to be triggered by the poor nucleophilicity of our alkoxide ligand (oCBhmp-). A very rare case of spontaneous resolution takes place on precipitation or exposure to solvent vapor for the bulk compound, as confirmed by a combination of single-crystal and powder X-ray diffraction, second-harmonic generation, and circular dichroism. The corresponding enantiopure complexes (+)1 and (-)1 have also been synthesized and fully characterized. This research provides a new building block with unique geometry and electronics to construct coordination complexes with multifunctional properties.